The thinness of the critical user of cocaine - Ana Laura Candil (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
Based on recent analytical perspectives about body, drugs and health, this article focuses on the description and analysis of one of the ways in which the body deterioration of intensive users of poor quality cocaine expressed, in the segregated neighborhoods of Greater Buenos Aires: the thinness. The approach is carried out from the ethnographic approach, from a fieldwork of two years, at a public institution approach to drug use. The techniques implemented were participant observation and semi-structured interviews and in depth.